Menilik Pelaksanaan Program Keselamatan dan Kesehatan Kerja : Fenomena pada Industri Stamping - Hananto, Adiel Amandus; Rahardja, Edy (Faculty of Economics and Business Diponegoro University, 2015)
This study aimed to identify the implementation of occupational safety and health programon an company and then to know the employees perception toward the implementation of occupational safety and health program. In this research the implementation of occupational safetyand health programs viewed through the seven elements namely the commitment of topmanagement, occupational safety and health training, personal protective equipment, supervision, work regulations and work procedures, safety signs and health services.This study use qualitative methods, where data collection is done by the interview. The main informan of this study were the employees from the safety health environment department and as the comparative subject were used from the employees that worked in the productiondepartment that already finished the training period for three months.Results obtained from this study states that three elements of the implementation of occupational safety and health program namely Commitment of Top Management, PersonalProtective Equipment and Health Service has been implemented properly and in accordance withwhat is required by employees. While the other four namely Occupational Safety and HealthTraining, Supervision, Work Procedure and Work Regulation, and the Safety Signs has not been properly implemented and still not in accordance with what is required by the employees.